Electronic data capture for large scale typhoid surveillance, household contact tracing, and health utilisation survey: Strategic Typhoid Alliance across Africa and Asia - Thindwa, D; Farooq, YG; Shakya, M; Saha, N; Tonks, S; Anokwa, Y; Gordon, MA; Hartung, C; Meiring, JE; Pollard, AJ; Heyderman, RS (F1000 Research Ltd, 2020)
Electronic data capture systems (EDCs) have the potential to achieve efficiency and quality in collection of multisite data. We quantify the volume, time, accuracy and costs of an EDC using large-scale census data from the STRATAA consortium, a comprehensive programme assessing population dynamics and epidemiology of typhoid fever in Malawi, Nepal and Bangladesh to inform vaccine and public health interventions.